Which Ladder to Climb? Decomposing Life Cycle Wage Dynamics - Christian Bayer; Moritz Kuhn (Institute of Labor Economics (IZA), 2019)
Wages grow and become more unequal as workers age. Economic theory focuses on worker investment in human capital, search for employers, and residual wage shocks to account for these life cycle wage dynamics. We highlight the importance of jobs: collections of tasks and duties defined by employers within the production process. We provide empirical evidence that climbing the career ladder toward jobs characterized by more responsibility, complexity, and autonomy accounts for the largest part of life cycle wage dynamics. It accounts for 50% of average wage growth, 50% of rising differences between gender, and virtually all of rising dispersion within gender over the life cycle.
Keywords: D33; E24; J31; 330; life cycle wage growth; wage inequality; career ladder